THE DECOMPOSITION KINETICS OF SOLIDS THERMODYNAMIC EVIDENCE FOR THE ENTHALPY DRIVEN COOLING OF REACTION ENVIRONMENT PART 2 - Akwilapo, L D; Kyobe, J. M. P; Buchweishaija, J. (Tanzania Journal of Engineering and Technology, 2018)
THE DECOMPOSITION KINETICS OF SOLIDS THERMODYNAMIC EVIDENCE FOR THE ENTHALPY DRIVEN COOLING OF REACTION ENVIRONMENT PART 2